Creative Thinking dalam Implementasi dan Rancang Bangun Multiple Sensors berbasis Plug-and-Play Systems with Database - Baskoro, Farid; Suprianto, Bambang; Anifah, Lilik; Ekohariadi; Nurdiansyah, Aristyawan; Rochman, Miftahur (JASEE Journal of Application and Science on Electrical Engineering, 2023)
The purpose of this study is to implement creative thinking from the aspect of innovation in developing multiple sensors in plug-and-play system with a database. The method used in this study was an experiment conducted by taking a sample of 5000 data. The location of the research was carried out in the telematics laboratory at Surabaya State University building A8 with room dimensions of 9 x 10 meters. The results of this study indicate a plug-and-play process developed by a scanning process to find connected PORTs without having to do configuration, showing a comparison of the DHT11 error value with a comparator that reaches 2.057 % on the temperature value, 0.829 % on the humidity value, 1.514 % on light intensity value, 1.429% on distance value, and provides 5000 data which includes temperature, humidity, light intensity, and distance data stored in database. Data on temperature, humidity, light intensity, distance, plug-and-play systems, GUI, and databases obtained by researchers are very useful for further research that will be developed to meet smart systems.